Self-secure feedback control based scheme for ultra-reliable and low-latency communication - Zheng Yang; Xiaofang Wang; Shuguang Lu; Jia Wang; Haoheng Yuan (PLoS ONE, 2026)
Ultra-reliable and low-latency communication (URLLC) is one of the key requirements in future wireless communications. In practical URLLC scenarios, an enhanced mobile broadband (eMBB) message together with an URLLC message are simultaneously encoded as codewords and transmitted over the same channels. Traditionally, the coding design of URLLC message often treats the eMBB codeword as interference corrupting the coding performance. In this paper, for the additive white Gaussian noise (AWGN) channel, we show that if noise-free channel feedback is available, there exists a feedback control based coding scheme for the URLLC message, which not only perfectly eliminates the interference caused by the eMBB codeword, but also approaches the maximum rate of the URLLC message when the codeword length tends to infinity. Furthermore, we show that this scheme satisfies the physical layer security requirement by itself, which indicates that our proposed scheme is a self-secure scheme. The results of this paper are explicitly explained by numerical examples, and this work provides a possible way to design efficient coding schemes for URLLC message transmission.